Identification of Novel CircRNA-miRNA-mRNA Regulatory Network and Its Prognostic Prediction in Breast Cancer - Rui Huang (Hindawi Limited, 2021)
Aim. This study aimed to investigate the expression profiles of circRNAs and candidate circRNA-miRNA-mRNA network in BC. Methods. Differentially expressed circRNAs, miRNAs, and mRNAs (DEcircRNAs, DEmiRNAs, and DEmRNAs) between BC and normal breast tissue samples were screened by analyzing raw data of the RNA sequencing profile. The expression levels of hub genes in 48 pairs of cancerous and tumor-free breast tissues surgically resected from BC patients were determined by RT-qPCR analysis. Results. A total of 145 DEcircRNAs, 140 DEmiRNAs, and 2451 DEmRNAs between BC and normal breast tissue samples were screened out. There were 5 pairs of upcircRNA-downmiRNA-upmRNA network and 20 pairs of downcircRNA-upmiRNA-downmRNA network. EIF4EBP1, DUSP1, EGR2, EZH1, and CBX7 were found to be correlated with overall survival of the patients with BC. The expression level of EIF4EBP1 was increased and the expression levels of DUSP1, EGR2, EZH1, and CBX7 were decreased in cancerous breast tissues compared to tumor-free breast tissues p<0.0001. The RT-qPCR results from 48 BC patients were consistent with the bioinformatics results. Conclusion. This study provides a novel perspective to study circRNA-miRNA-mRNA network in BC and assists in the identification of new potential biomarkers to be used for diagnostic and prognostic purposes.